Cognitive behaviour therapy for dental phobia and anxiety - Ost, Lars-Goran; Skaret, Erik (Chichester, West Sussex, UK : Wiley-Blackwell, 2013)
'The book is meant to help students and professionals in dentistry to understand the complexity of the anxiety phenomenon, and in psychology to understand the specific situation for the dental phobia (DP) patient, and bridge the gap between dentistry and psychology'--
Includes bibliographical references and index.
Keywords: Fear of dentists; Cognitive therapy; Evidence-based dentistry; Dentist and patient